Pengembangan Media Video Tutorial Sulaman Pita Pada Elemen Desain Hiasan Di SMKS Dharma Wanita Gresik - Amelya Nur Listyani; Imami Arum Tri Rahayu; Urip Wahyuningsih; Mita Yuniati (Journal Innovation In Education, 2024)
This research aims: (1) To determine the feasibility of video tutorial media for ribbon embroidery on decorative design elements for class XI students at SMK Dharma Wanita Gresik (2) To determine the response of class Gresik Women. The research was carried out at Surabaya State University. The type of research used is quantitative descriptive. This research method uses R&D or Research and Development. This research instrument uses material suitability tests, media suitability and student responses. The results of this research state that: (1) the level of feasibility of developing ribbon embroidery tutorial video media by media experts and material experts is an average of 3.35 with a feasible category (2) student responses to developing ribbon embroidery video tutorial media The total percentage score obtained is above 94% is categorized as very good.